Stall in low hub tip ratio industrial fans - Yu, H. (Cranfield University, 1991)
This thesis presents the experimental investigation of stall in low hub tip ratio industrial fans. Detailed measurements were obtained i four fan configurations. The effects of blade setting angle, solidity, blade profile and OGVs on rotating stall were investigated. The purpose of this work has been to get a better understanding of stall i low hub tip ratio fans. A fan test rig was built specially for this investigation. A three hole pressure transducer probe was made to measure the velocity and pressure at rotating stall conditions. A data acquisition system was developed to ensure the results of better quality. Blade Vibration was also monitored at different flow conditions for two builds. From the results obtained, some important features of rotating stall were observed. For the fans with a low blade setting angle, there was no rotating stall. The overall characteristics were continuous. For the fans with high blade setting angle, rotating stall appeared within a limited flow range. The rotating stall cells i the fans were always a single stall cell, covering part of the rotor tip region. The characteristics were the abrupt type. V A Detailed traverse measurements show that rotating stall has a very strong influence on the flow upstream of the rotor and has little effect on the flow downstream. The effects of space chord ratio, blade profile and OGVs on the stall behaviour have also been investigated. The experimental results also indicate that hub tip ratio has a important effect on the rotating stall behaviour. It is therefore concluded that the stall models based on the observation of high hub tip ratio compressors are not applicable to low hub tip ratio fans. The time averaged measurements show that a large radial shift of streamlines exist i the low hub tip ratio fans. Reverse flow near the hub downstream of the rotor was found in many cases, but reverse flow near the hub does not trigger rotating stall. However, the large low velocity region near the hub will affect the fan steady state performance. A simple streamline curvature program has been used to analyse the endwall boundray layer effect on the fan performance. \ Axisymmetric stall is important i low hub tip ratio fans because it dominates most of the stalled flow conditions. Axisymmetric stall is preferred to rotatíng stall since it gives the continuous type characteristic and it causes less Vibration problem. A set of nonlinear equations is used to simulate axsiyrnmetric stall a well a rotating stall and surge.